The rights of asylum seeking children: integrating the child’s best interests principle through interpretation - Ioffe, I (2020)
Today about half of the world’s refugee population are children. The ensuing need for protection of children seeking asylum has been sought to be addressed by international law through various international treaties, including the Convention relating to the Status of Refugees, the International Covenant on Civil and Political Rights, the Convention on the Rights of the Child, the European Convention on Human Rights, and the American Convention on Human Rights. Most of these treaties, however, are age-neutral and do not afford special protection to asylum seeking children. This has prompted the international institutions (both adjudicative and norm-setting ones) to interpret the rules related to asylum seeking children through an ‘adult-focused lens’, resulting in the misinterpretation of the rules and the development of age-insensitive jurisprudence and norm-setting practice. This thesis examines the interpretation of key rights, which are particularly important to children seeking asylum, namely the rights to liberty and family life, by five international institutions (the Committee on the Rights of the Child, the Human Rights Committee, the European Court of Human Rights, the Inter-American Court of Human Rights, and the United Nations Refugee Agency). The thesis argues that the misinterpretation of the rules providing for these rights may be addressed by greater interaction between the international institutions, and specifically through the reference, in the course of interpretation, to an age-sensitive treaty, the Convention on the Rights of the Child. The child’s best interests principle, which is reflected in Articles 3 and 9, is a unique provision to the Convention on the Rights of the Child and should play a central role in the interpretation of the rights of asylum seeking children. The thesis answers both a descriptive question of what the current interpretative practice of these international institutions is, and a normative question of whether the international institutions pay appropriate attention to the child’s best interests principle. The thesis relies on two arguments, the systemic integration principle and the most favourable approach. It concludes that giving due weight to the child’s best interests principle leads to the most favourable interpretation of the rights to liberty and family life of asylum seeking children.